(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2023)
To scrutinize the present status of birds in a sub-tropical urban green space, a research work was conducted in Mymenshing City Corporation from November 2018 to October 2019 by direct field observations. Three green spaces were selected in the study area where in total 180 species of birds with 7,079 individuals were documented. Passeriformes had the highest species richness (76 species, 42.22%) and abundance (n = 4174, 58.96%). Bangladesh Agricultural University Campus Area (Site A) showed the highest diversity index value with the highest species richness (170 species, 94.44%) and abundance (n = 3261, 46.06%). Analysis of similarity (ANOSIM) test showed a significant difference in bird communities among three study sites. Cluster analysis showed that fallow land and agricultural land formed a large cluster which further formed another cluster with grassland, water-body, tree and urban settlements. Species richness and abundance across the seasons and study sites varied significantly. The highest avian diversity and abundance were observed in winter, particularly in January. Species richness and abundance for nine microhabitats showed significant variations where tree was mostly used microhabitat. The avian community of urban settlements and agricultural lands were highly correlated. These urban green spaces support 48 (26.67%) migratory birds in the study area. Pycnonotus cafér had the highest relative abundance (4.28%), Maximum observed bird species as the least concern and five species were threatened according to the national conservation status. J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(2): 37-50